Understanding Foot Loading and Balance Behavior of Children with Motor Sensory Processing Disorder - Lin Yu; Peimin Yu; Wei Liu; Zixiang Gao; Dong Sun; Qichang Mei; Justin Fernandez; Yaodong Gu (MDPI AG, 2022)
Sensory processing disorder (SPD) could influence the neuromuscular response and adjustment to external sensory discrimination and lead to disruptions in daily locomotion. The objective of the current study was to compare plantar loadings and foot balance during walking, running and turning activities in SPD children in order to reveal the behavioral strategy of movement and balance control. Six SPD children and six age-match healthy controls participated in the test using a FootScan plantar pressure plate. The time-varying parameters of forces, center of pressure and foot balance index were analyzed using an open-source one-dimensional Statistical Parametric Mapping (SPM1d) package. No difference was found in foot balance and plantar loadings during walking, while limited supination-pronation motion was observed in the SPD children during running and turning. The plantar forces were mainly located in the midfoot region while less toe activity was found as well. Findings should be noted that SPD children had limited supination-pronation movement for shock attenuation in the foot complex and reduced ankle pronation to assist push-off and toe gripping movements. Understanding the behavior of plantar loading strategy and balance control during walking, running and turning activities may provide clinical implications for the rehabilitation and training of daily tasks.